Multiscale Structural Elucidation of Peptide Nanotubes by X-Ray Scattering Methods - Narayanan, Theyencheri; Rüter, Axel; Olsson, Ulf (Frontiers in Bioengineering and Biotechnology, 2021)
This mini review presents the structural investigations of the self-assembled peptide nanotubes using X-ray scattering techniques. As compared to electron microscopy, scattering methods enable studies of nanotubes in solution under the appropriate physicochemical conditions and probe their formation mechanism. In addition, a combination of X-ray scattering methods allow the elucidation of structural organization from the molecular scale to the dimension of nanotubes.